Handbook of research on financial management during economic downturn and recovery - Teixeira, Nuno Miguel, 1974-; Lisboa, Ines Margarida, 1981- (Business Science Reference, 2021)
"This book provides and shares knowledge about challenges in the way that companies, financial markets, financial institutions and governments respond to a pandemic situation that create big changes in the lives of people, organizations and countries"--